Migrate, Publish, Repeat: TEI Journals in the Open Journal Systems Platform - Nicholas Homenda; Shayna Pekala (Journal of the Text Encoding Initiative)
The Indiana University (IU) Libraries have a long history of using the TEI markup standard to encode and publish electronic texts, but choosing the best publishing platform has been challenging for certain projects. Before formally launching an open access journal publishing program in 2008, the Libraries collaborated with two scholarly journals to provide open access publishing using P3 SGML and P4 XML TEI encoding delivered through the DSpace and XTF platforms. Both journals used complex encoding, transformation, and delivery workflows that required copious amounts of custom software development to function properly. As these systems aged, the time and effort required to maintain them steadily increased. In 2013, the Libraries began planning to migrate these journals into the Open Journal Systems (OJS)1 platform while preserving the TEI markup. Both journals are now publishing using the OJS platform. The Indiana Magazine of History2 was successfully launched in OJS in August 2014, and The Medieval Review3 was launched in June 2015. Publishing in this manner leverages the IU Libraries’ strengths in electronic text projects and XML workflows within an easy-to-use, flexible platform that journal editors appreciate. The success of these migrations presents a new framework for future XML publishing of open access journals at Indiana University.